Paleoenvironmental Reconstruction of the Sentolo Formation Based on Paleosalinity and Paleoproductivity, South Serayu Basin, Indonesia - Esti Solehatun; Ihstar Andin Nur Fatiq; Sapto Kis Daryono (Journal of Earth and Marine Technology (JEMT), 2026)
The Sentolo Formation represents one of the stratigraphic units of the Kulon Progo Mountains within the South Serayu Basin and is distinguished by the widespread occurrence of limestone. This formation is interpreted to have been deposited in marine settings ranging from neritic to bathyal environments, thereby preserving valuable palaeoceanographic information that can be used to reconstruct past ecological conditions. The distribution of foraminiferal assemblages in the Sentolo Formation is closely controlled by environmental factors, with particular species serving as proxies for ecological parameters such as palaeosalinity and palaeoproductivity. Analysis of the planktic foraminifera Orbulina universa and Globigerinoides sacculifer suggests that palaeosalinity conditions during deposition ranged from brackish to normal marine. In addition, reconstruction based on benthic foraminiferal assemblages indicates oligotrophic palaeoproductivity, as reflected by the predominance of epifaunal taxa over infaunal taxa. Brackish to normal marine salinity conditions are inferred to have promoted relatively high oxygenation, which may have limited the preservation of organic matter. The resulting low accumulation of organic material, together with evidence of oligotrophic productivity, indicates that the Sentolo Formation has limited potential as a hydrocarbon source rock.